Epidemiology of musculoskeletal disorder among surgeons: a systematic review - Baraskar, Shamika S.; Borkar, Pradeep (International Journal of Research in Medical Sciences, 2022)
Surgeons spend most of their working time in ergonomically challenging postures. These postures lead to musculoskeletal pain. WRMD’s consists various symptoms like pain, fatigue, stiffness, weakness. A significant prevalence of neck, shoulder, back and wrist pain has been reported among surgeons. The aim of the study was to study Epidemiology of Work-Related Musculoskeletal Disorders Among Surgeons. Article systematically reviews epidemiology studies on musculoskeletal disorder among surgeons, literature search was undertaken using google scholar, PubMed, Medline and ScienceDirect from last 10 years from 2012 to 2022. Total 11 studies were included. We applied the checklist, Strengthening the Reporting of Observational studies in Epidemiology (STROBE), to assess the quality of reporting of the included studies. A total of 50 articles were identified. Exclusion criteria lead to 26 full-text articles being screened, generating a total of 11 articles for review. Seven cross sectional studies, two cohort studies and two observational studies were included. Based on analysis of included studies, most of the study stated high prevalence of cervical spine diseases among surgeons. They should represent a major step forward in prevention of WRMSDs among surgeons.